Primary school EFL teachers’ use of the pilot textbook series : - Nguyễn, Kim Thư (Trường Đại học Cần Thơ, 2019)
This study aimed at using of primary EFL textbook series for the 3rd graders 4th graders and 5th graders are English 3, English 4 and English 5 by Vietnam National Education Publishing House about the curriculum of primay school EFL teachers in Kien Giang Province. Participants consist of 60 primary school EFL teachers. The tool of study designed to cover the quantity of textbook content that primary school EFL teachers use for their teaching and the reasons for the teachers’ selection for such section from the book.